Evaluation of response quality for heterogeneous question answering systems - Wong, W.; Sahib, S.; Goh, Ong Sing (IEEE, 2005)
The research in this paper makes explicit why existing measures for response quality evaluation is not suitable for the ever-evolving field of question answering and following that, a short-term solution for evaluating response quality of heterogeneous systems is put forward. To demonstrate the challenges in evaluating systems of different nature, this research presents a black-box approach using a classification scheme and scoring mechanism to assess and rank three example systems.